2019
DOI: 10.1149/2.0011912jes
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Storage Derived Surface Contamination of NCM811 and NCM111: Performance Implications and Mitigation Strategies

Abstract: The quality of metal oxide-based battery active materials is compromised by surface contamination from storage and handling at ambient conditions. We present a detailed analysis of the true nature and the quantity of the surface contaminants on two different cathode active materials, the widely used LiNi1/3Co1/3Mn1/3O2 (NCM111) and the Ni-rich LiNi0.8Co0.1Mn0.1O2 (NCM811). We process these materials in three distinct conditions “wet” (excessive exposure to moisture), “dry” (standard drying of as-received mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
222
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(231 citation statements)
references
References 52 publications
9
222
0
Order By: Relevance
“…851005.-To study the washing process, we selected the Ni-rich cathode material NCM-851005, as it is known that the formation of surface contaminants, such as LiOH and Li 2 CO 3 , is most pronounced and has the most detrimental effect on cycle-life for nickel-rich materials. 8,9,22 In order to obtain accurate values for the amounts of adsorbed LiOH and Li 2 CO 3 from the titration analysis of the filtrate after the first washing step as well as for their possible formation in the second washing step, the washing process for the following set of washing experiments was carried out in an argon-filled glove box in order to exclude any effects of CO 2 from the air. Figure 1a shows the lithium carbonate content determined by titration of the washing filtrate.…”
Section: Co 3 and Lioh Release And Ph-value During Washing Of Ncm-mentioning
confidence: 99%
See 1 more Smart Citation
“…851005.-To study the washing process, we selected the Ni-rich cathode material NCM-851005, as it is known that the formation of surface contaminants, such as LiOH and Li 2 CO 3 , is most pronounced and has the most detrimental effect on cycle-life for nickel-rich materials. 8,9,22 In order to obtain accurate values for the amounts of adsorbed LiOH and Li 2 CO 3 from the titration analysis of the filtrate after the first washing step as well as for their possible formation in the second washing step, the washing process for the following set of washing experiments was carried out in an argon-filled glove box in order to exclude any effects of CO 2 from the air. Figure 1a shows the lithium carbonate content determined by titration of the washing filtrate.…”
Section: Co 3 and Lioh Release And Ph-value During Washing Of Ncm-mentioning
confidence: 99%
“…6,7 It was shown that Ni-rich materials are very sensitive toward storage under humidity and CO 2 containing atmospheres, [6][7][8][9] leading to the formation of large amounts of hydroxides and carbonates on the surface of the CAM particles. [10][11][12][13][14][15][16][17] These surface impurities do not only lead to a deterioration of the capacity retention 6,8,9 and to substantial gassing during cell cycling, 8,[18][19][20][21] but also lead to a high pH of the electrode coating slurries, which can cause gelation of the slurry during electrode preparation. 17,22 A simple and practical approach to remove surface contaminants taken by cell and material manufacturers is a washing step, in which the cathode active material is washed in an aqueous solution.…”
mentioning
confidence: 99%
“…[12][13][14][15] Significant efforts in developing high-Ni NMC cathodes have been put on studying electrochemical impact, origin of the Li/ Ni disordering, and on improving Li/Ni ordering through optimizing synthesis conditions. [23] These surface species are electrochemically inactive and poor in electronic and ionic conductivity, so causing high impedance to Li + (de)intercalation during cycling, [24,25] and even power fade as reported in LiNi 0.8 Co 0.2 O 2 . [23] These surface species are electrochemically inactive and poor in electronic and ionic conductivity, so causing high impedance to Li + (de)intercalation during cycling, [24,25] and even power fade as reported in LiNi 0.8 Co 0.2 O 2 .…”
Section: (2 Of 10)mentioning
confidence: 99%
“…[1,2] In particular, high-Ni layered oxides, LiNi x Mn y Co z O 2 (NMC; x ≥ 0.7) are now attracting world-wide interest for their high theoretical capacity (≈280 mA h g −1 ), which, however, has been difficult to realize due to the issues associated with high Ni loading: [3][4][5][6][7][8] in addition to cationic disordering (Li/Ni mixing) and the resulted low electrochemical activity, [9][10][11] Transition metal layered oxides have been the dominant cathodes in lithiumion batteries, and among them, high-Ni ones (LiNi x Mn y Co z O 2 ; x ≥ 0.7) with greatly boosted capacity and reduced cost are of particular interest for largescale applications. [23] These surface species are electrochemically inactive and poor in electronic and ionic conductivity, so causing high impedance to Li + (de)intercalation during cycling, [24,25] and even power fade as reported in LiNi 0.8 Co 0.2 O 2 . The rational design of synthesis leading to layered LiNi 0.7 Mn 0.15 Co 0.15 O 2 with greatly enhanced rate capability is demonstrated, by implementing a quenching process alternative to the general slow cooling.…”
mentioning
confidence: 99%
“…Sicklinger et al showed how the top layer of the secondary particles usually consists of surface contaminations such as hydrated nickel carbonate-hydroxides or Li 2 CO 3 due to air exposure (which cannot be fully prevented due to the synthesis and storage conditions used for the commercial sample). 26 Usually such surface contaminants result in a more reduced top surface layer. This can be probed by auger electron yield (AEY, 2 nm), but this was not used in this study because the oxidation state is strongly affected by surface contaminants.…”
Section: Inherent Stability Of LI 03 Nca At Operating Conditions Of mentioning
confidence: 99%